A review on the infrastructure and tool support for Model-Driven Engineering in the automation of the petrochemical industry - Correia, Carlos Eduardo Xavier; Becker, Leandro Buss; Basso, Fabio Paulo (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS), 2023)
Automation is a fundamental part of the oil industry, responsible for ensuring productivity and process safety. The application of control systems is carried out through different software applications, which are often unable to exchange data (models) within each other. This is a significant limitation for the overall design process. To address this issue, the use of the Model-Driven Engineering for Petrochemical Industry Automation (M4PIA) platform is proposed. M4PIA is capable of accommodating the software applications Automated Procedures Module (MPA) and Environment for Modeling, Simulation, and Operation (EMSO), both of which are used by the Brazilian state-owned company Petrobras.